Trading-off the income gains and the inequality costs of trade policy - Erhan Artuc; Guido G. Porto; Bob Rijkers (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2018)
This paper characterizes the trade-off between the income gains and the inequality costs of trade using survey data for 54 developing countries. Tariff data on agricultural and manufacturing goods are combined with household survey data on detailed income and expenditure patterns to estimate the first order effects of the elimination of tariffs on household welfare. We assess how these welfare effects vary across the distribution by estimating impacts on the consumption of traded goods, wage income, farm and non-farm family enterprise income, and government transfers. For each country, the income gains and the inequality costs of trade liberalization are quantified and the trade-offs between them are assessed using an Atkinson social welfare index. We find average income gains from liberalization in 44 countries and average income losses in 10 countries. Across countries in our sample, the gains from trade are 1.8 percent of real household expenditure on average. We find overwhelming evidence of a trade-off between the income gains (losses) and the inequality costs (gains), which arise because trade tends to exacerbate income inequality: 46 countries face a trade-off, while only 8 do not. These trade-offs are typically resolved in favor of lower tariffs. In the majority of developing countries, the prevailing tariff structure thus induces sizeable welfare losses.
Keywords: 330